Use of comprehensive geriatric assessment (CGA) to define frailty in geriatric oncology: Searching for the best threshold. Cross-sectional study of 418 old patients with cancer evaluated in the Geriatric Frailty Clinic (G.F.C.) of Toulouse (France). Issue 6 (November 2019) - Bréchemier, Delphine; Sourdet, Sandrine; Girard, Philippe; Steinmeyer, Zara; Mourey, Loic; Gérard, Stéphane; Balardy, Laurent
Abstract: Objectives: A consensual and operational definition of frailty is necessary in geriatric oncology. While many studies have focused on geriatric syndromes evaluated in the comprehensive geriatric assessment (CGA) to select patients at higher risk of poor outcomes, few have compared CGA data with Fried's phenotype of frailty, the most consensual measurement of frailty in geriatrics. Our objective was to determine a threshold of impaired domains evaluated in CGA associated with Frailty status. Methods: A cross-sectional study including all patients with cancer, evaluated from January 2011 to February 2016 at the Geriatric Frailty Clinic, Toulouse. A CGA was performed evaluating seven geriatric domains. Frailty was measured by Fried's phenotype to classify patients into three groups (robust/pre-frail/frail). We plotted a ROC curve to determine the threshold of impaired domains associated with frailty according to Fried. Results: We included 418 patients aged 82.8 years (range 66–100 years). Thirty-three patients (7.9%) were robust, 155 (37.1%) pre-frail and 230 (55%) frail. There was a significant difference in ADL, IADL, nutrition, cognition and polypharmacy between the three groups (p < .001 for each domain). Frail patients had more impaired geriatric domains on CGA than pre-frail and robust patients (respectively 4.5 ± 1.5, 2.8 ± 1.6 and 2.1 ± 1.2; p < .001). The threshold of 4 impaired geriatric domains associated with Fried's Frailty status was identified (Se 77.39%, Sp 67.55%). Area under the curve was 79.6%. Conclusion: The phenotype of frailty is associated with more impaired geriatric domains and a threshold of 4 altered domains could be used to detect frailty from CGA data.